Social Mobility And Struggle For Women's Right To Choose Spouses In Jane Austen's Persuasion - Kumala, Achmasepti; , Dr. Phil. Dewi Candraningrum, M.Ed; , Dr. M. Thoyibi, M.S (2013)
This research aims at: (1) finding out the effects of social mobility in the novel to the changing of human thoughts and attitudes; (2) scrutinizing the female main character's struggle for her right to choose her spouse; and (3) revealing the relation of British social background in nineteenth century and Jane Austen's Persuasion's story. The qualitative research is carried out by making use of the descriptive method. The researcher analyzes the data by using feminist and sociology of literature. The analysis is used for: describing the extrinsic elements of the novel including the background of the novel's production and Jane Austen's life; analyzing the psychological motivations of changing thought and attitudes of each character of the novel. Based on the result of the data analysis, the research findings are: (1) The social mobility happens in Austen's Persuasion. brings about some influences to the characters' attitudes and thought; (2) the female main character do some struggles for obtaining her right to choose her spouse; (3) there is a close relation between the Jane Austen's Persuasion and its context of production in the nineteenth century. The result of this research implies that the there are some significant changing on human thought and attitudes in Jane Austen's Persuasion; there some efforts done by the female main character to struggle for her right to choose her spouse and the last, there is a close relation between Jane Austen's Persuasion and its context of production